ORIGINAL ASPECTS REGARDING THE MONITORING AND DIRECTING OF THE EFFORT OF STUDENTS OF THE UNIVERSITY OF BUCHAREST, WITHIN THE LESSONS OF NAUTICAL SPORTS ACTIVITIES (University Arena, 2025)
Background. Through its specific objectives and tasks, nautical sports activities contribute to the psycho-somatic and social development of practitioners, becoming a discipline beloved by students, they number increasing from year to year. This discipline, shortly introduced in the DEFS 'curriculum, responded to a need to diversify the socio-educational interests of University of Bucharest` students, the University of Bucharest being the only university in the country that does not have a sports profile, which offers such lessons to its students.Objectives. The present paper, through its content and its approach, aims to highlight the main aspects of the specific effort, applied and recorded in kayak lessons. The subject is Dang Huan Fang, student at the Faculty of Geology and Geophysics, 1st place holder in two important competitions organized this year: the "Alexandru Bizim" University Cup and the Kayak Challenge 2025.Methods. Our scientific approach aimed, mainly, at presenting some model trainings, specific to the preparatory period, with the objective of developing endurance through specific and non-specific means for the 1000m kayak race.Results. The information provided by the Garmin Fenix 5 device used in this research contributes decisively to optimizing the planning and programming strategy of the practical activity of students enrolled in the nautical sports activities discipline, constituting essential feedback for those directly and indirectly involved in the training process.The obtained data are based on objective, efficient and modern monitoring, used for the first time at the level of non-profile higher education, thus providing an overview of the specific demand for these activities.Conclusion. Through its content, our project emphasizes the importance and opportunity of using modern and efficient means of monitoring the parameters of the effort specific to the 1000m kayak race, all in the context of a general strategy for training UB students, practitioners of the race referred to previously, which should have as a starting point a particular training model, based on modern means, adapted to the particularities of the race and the motor profile of the practitioners.
Keywords: monitoring; nautical sports activities; students